Growth and characterization of butyl 4-hydroxybenzoate single crystal by vertical Bridgman technique for third order nonlinear optical applications. (February 2017) - Arivazhagan, T.; Siva Bala Solanki, S.; Rajesh, Narayana Perumal
Abstract: The butyl 4-hydroxybenzoate single crystal has been grown by vertical Bridgman technique using single wall ampoule. The cell parameters of the grown crystal are verified by single crystal X-ray diffraction analysis. The functional groups of the grown crystal were identified by Fourier transform infrared analysis. The melting, decomposition and crystallization point of the compound are determined by thermo gravimetric analysis and differential scanning calorimetric analysis. The mechanical properties of the grown crystal has been analyzed by Vickers microhardness method. The optical behavior of the grown crystal has been observed by UV–vis–NIR transmission spectroscopic analysis which shows that the lower cut-off wavelength lying at 293 nm and found that the energy band gap value is 4.05 eV. The blue light emission of the crystal was identified by photoluminescence studies. The positive third order nonlinear optical parameters like nonlinear refractive index (n2 ), nonlinear absorption co-efficient (β) and third order nonlinear susceptibility (χ 3 ) of the grown crystal was calculated by Z-scan studies. The positive sign of nonlinear refractive index (n2 ) indicates that the crystal exhibits self focusing optical nonlinearity. The crystal exhibits good optical power limiting behavior. Graphical abstract: Highlights: Butyl 4-hydroxybenzoate single crystal was grown by vertical Bridgman technique. The band gap value of the grown crystal is estimated as 4.05 eV. The PL emission at 430 nm suggests that it is a blue light emitting material. The n2 and χ 3 values of crystal are 1.585×10 −11  m 2 /W and 7.264×10 −6  esu respectively. Two photon absorption of the crystal is attributed for optical limiting applications.